Polymorphism of SLC11A1 gene in Doom pigs of Asom - DEVI, BHANITA; LASKAR, S; BORAH, P; KALITA, D J; ZAMAN, G U; FERDOCI, A M; HUSSAIN, I (The Indian Journal of Animal Sciences, 2015)
The solute carrier family 11 member 1 (SLC11A1) also called as NRAMP1 gene is found to be associated with the transport of iron and other bivalent cations. To find out polymorphism in SLC11A1 gene in Doom pigs of Asom, 55 blood samples were collected randomly from Doom pigs and genomic DNA was extracted using the rapid isolation of mammalian DNA method. A fragment of 934 bp length of SLC11A1 gene was amplified using polymerase chain reaction (PCR) with a pair of specific primers. The amplified PCR products of SLC11A1 gene was digested with SmaI restriction enzyme, which produced 3 fragments (505bp, 231bp and 198bp), 4 fragments (505bp, 429bp, 231bp and 198bp) and 2 fragments (505bp and 429bp) for AA, AB and BB genotypes, respectively. At position 736, A↔G transition was found for AB genotype. The present study revealed that the population of Doom pigs under study was polymorphic in respect of SLC11A1 gene having 2 alleles with frequencies 0.8364 and 0.1636 for ‘A’ and ‘B’, respectively. The genotypic frequencies were 0.71, 0.26 and 0.03 for AA, AB and BB genotypes, respectively.